2016
DOI: 10.1182/blood.v128.22.1057.1057
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Inhibition of PI3Kδ and PI3Kα Induces ABC-DLBCL Regression Via Attenuation of BCR-Dependent and Independent Activation of NF-Kb and AKT

Abstract: Introduction: ABC-DLBCL is a subtype of DLBCL with less favorable clinical outcomes to the standard of care (SoC) therapies. Constitutive activation of NF-κB by various genetic alterations in ABC-DLBCL has been identified as one of the key mechanisms driving chemotherapy resistance. Inhibition of B cell receptor (BCR) signaling with BTK (Bruton's tyrosine kinase) inhibitor ibrutinib demonstrated encouraging clinical responses in ABC-DLBCL. However, patients with CD79wt/MyD88mut, or CARD11mut did not respond to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The B cell receptor (BCR) can activate several pathways, including NF-κB, MEK/ERK, and PI3K/AKT, which regulate B-cell apoptosis and proliferation [99] (Figure 5). The chronic activation of BCR was found in lymphomas and it was reported that ABC-DLBCL cancer cells escape apoptosis through the NF-κB signaling pathway [100].…”
Section: B Cell Receptor-mediated Signalingmentioning
confidence: 99%
“…The B cell receptor (BCR) can activate several pathways, including NF-κB, MEK/ERK, and PI3K/AKT, which regulate B-cell apoptosis and proliferation [99] (Figure 5). The chronic activation of BCR was found in lymphomas and it was reported that ABC-DLBCL cancer cells escape apoptosis through the NF-κB signaling pathway [100].…”
Section: B Cell Receptor-mediated Signalingmentioning
confidence: 99%